Dialektika Hukum dan Moral dalam Perspektif Filsafat Hukum - Salman Luthan (Fakultas Hukum Universitas Islam Indonesia, 2012)
The research aims to study the dialectics between law and moral in the perspective of legal philosophy and examine the function of moral for law and law for moral. This study is a doctrinal-legal research that uses primary legal materials and a conceptual-juridical approach. The result indicates that the relationship between law and moral bears a reciprocal functional relation in law making and law enforcement. For law, moral functions as the source of ethics (values) in positive law making, source of rules in positive law, evaluative instrument for legal rule substances, and justification reference for settlement of legal cases that have unclear laws. Meanwhile, for moral, law functions as a medium that transforms individual moral rules into social legal rules with certain sanctions, strengthens moral values, principles, and rules, establishes new morality in the society, and enforce moral values, principles, and rules in social order.